A Mediation Analysis of Digital Engagement on the Influence of Exposure to HIV/AIDS Educational Content on TikTok on Adolescents' Knowledge - Tirtawati, Gusti Ayu; Ediyono, Suryo (Oshada, 2025)
Advances in digital technology have driven significant transformations in adolescents' information consumption patterns, particularly through short video-based platforms like TikTok. This medium serves not only as a space for entertainment but also as an effective educational platform for conveying health messages, including on the issue of HIV/AIDS, which still faces social stigma. This study aims to analyze the relationship between exposure to HIV/AIDS educational content on TikTok and increased adolescent knowledge, and to examine the role of digital engagement as a mediating variable in this process. Using a qualitative approach with a literature review method, this study combines narrative and thematic synthesis to comprehensively interpret empirical and conceptual results. The results indicate that digital engagement, such as commenting, sharing, or recreating content, plays a crucial role in strengthening the internalization of health messages through a reflective and participatory process. Repeated exposure to creatively and emotionally packaged educational content can enhance adolescents' understanding and critical awareness of HIV/AIDS. However, the challenge of misinformation demands increased digital literacy to ensure the credibility of messages received. The implications of this study emphasize that effective digital health education strategies require collaboration between health workers, educators, and content creators to create an interactive, inclusive, and evidence-based learning environment in the digital era.